Expressions of IGFBP-5, cFLIP in cervical intraepithelial neoplasia, cervical carcinoma and their clinical significances: a molecular pathology - Hou, Xue-Jing; Zhang, You-Zhong; Liu, Xin; Meng, Li-Hua; Qiao, Yun-Bo (Journal of experimental & clinical cancer research, 2009)
Insulin-like growth factor binding protein (IGFBPs) have been as potential tumor suppressors in the occurrence and development of tumors. Cellular Fas-associated death domain-like interleukin-1beta-converting enzyme (FLICE)-like inhibitory protein (cFLIP) contains a death effect domain (DED), which blocks death receptor pathway and inhibits apoptosis. We collected normal cervical tissues from 28 subjects, CIN samples from 37 patients, and cervical cancer tissues from 40 patients. In these samples, we then measured the expression levels of IGFBP-5 and cFLIP via RT-PCR and immunohistochemistry, and we detected the presence of high-risk HPV by Hybrid capture II assays in cervical secretions provided by the subjects. significant differences in the expression of IGFBP-5 protein among the normal, CIN, and CC tissues (P < 0.05). The highest expression of IGFBP-5 protein was found in CIN stage II and III tissues, whereas the expression of IGFBP-5 in CC samples was decreased relative to controls. The expression level was affected by factors such as clinical stage, pathological differentiation, and lymph node metastasis. Relative to the controls, IGFBP-5 mRNA content was higher in the CC group and lower in the CIN group (P < 0.05). No expression of cFLIP protein or mRNA was detected in normal cervical tissues. However, the degree of pathological changes correlated with increasing expression of cFLIP protein and mRNA, and significant differences were therefore detected between groups (P < 0.05). The HPV infection rates in the CIN and CC groups were much higher than in the normal group (P < 0.05). IGFBP-5 expression is up-regulated in response to progression of CIN and down-regulated in invasive cervical carcinoma. Detection of IGFBP-5 and cFLIP expression levels, may prove particularly useful for diagnosing and differentiating CIN and CC.